ChemInform Abstract: EuAu3Al2: Crystal and Electronic Structures and Spectroscopic, Magnetic, and Magnetocaloric Properties. Issue 46 (October 2016) - Schmiegel, Jan‐Patrick; Block, Theresa; Gerke, Birgit; Fickenscher, Thomas; Touzani, Rachid St.; Fokwa, Boniface P. T.; Janka, Oliver
Abstract: The title compound is synthesized from the elements (Ta ampule, 1300 K for 10 min and 825 K for 2—8 h) and characterized by single crystal XRD, Moessbauer spectroscopy, magnetic measurements, and DFT calculations.